Gilbert or Crigler–Najjar syndrome? Neonatal severe unconjugated hyperbilirubinemia with P364L UGT1A1 homozygosity - Laura Cozzi; Federica Nuti; Irene Degrassi; Daniela Civeriati; Giulia Paolella; Gabriella Nebbia (Italian Journal of Pediatrics, 2022)
Abstract Background Several mutations of bilirubin uridine diphosphate-glucuronosyltransferase gene (UGT1A1) have been reported in patients with unconjugated hyperbilirubinemia. Few reports are available about the p.Pro364Leu mutation (P364L, c.1091C > T) in homozygous newborns. We describe the clinical, laboratory and therapeutic approach in two Chinese neonates with severe jaundice, homozygous for the P364L mutation. Case presentation Two Chinese breastfed female infants presented prolonged unconjugated hyperbilirubinemia at the age of 1 month. Total bilirubin was higher than 15 mg/dl (D < 1). An exhaustive etiological work-up to detect possible causes of hyperbilirubinemia (notably hemolytic ones) was negative. The promoter and coding regions of UGT1A1 were amplified by polymerase chain reaction (PCR) from genomic DNA isolated from leukocytes. Both patients resulted homozygous for a variant site within the coding region of the gene in the 4 exon, c.1091C > T, p.Pro364Leu. In front of the persistently high level of unconjugated bilirubin, phototherapy was performed without persistent results. A treatment with phenobarbital was then begun and bilirubin level progressively decreased, with a complete and persistent normalization. The therapy was stopped. Conclusion UGT1A1 enzyme activity associated with the P364L mutation has been described as 35.6% of the wild-type enzyme activity. Photo-therapy and phenobarbital can be useful in front of persistently high level of unconjugated bilirubin. Our cases presented high bilirubin values, overlapping between Gilbert syndrome (GS) and Crigler-Najjar syndrome type II (CNS), but the complete normalization of bilirubin makes GS more likely. Homozygous P364L variant can be associated with severe neonatal unconjugated hyperbilirubinemia in Chinese infants, but jaundice can completely resolve in a few months, contrary to what happens in Crigler-Najjar syndrome type II.